2007
DOI: 10.1128/aem.02014-06
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Accumulation of Mutants in a Biofilm Reflects Natural Selection Rather than Stress-Induced Adaptive Mutation

Abstract: The accumulation of mutant genotypes within a biofilm evokes the controversy over whether the biofilm environment induces adaptive mutation or whether the accumulation can be explained by natural selection. A comparison of the virulence of two strains of the dental pathogen Streptococcus mutans showed that rats infected with one of the strains accumulated a high proportion (average, 22%) of organisms that had undergone a deletion between two contiguous and highly homologous genes. To determine if the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…S. mutans is organized on biofilms, where the cells are closely packed together and multiple species of microorganisms coexist. A previous study indicates that the S. mutans WIG Ϫ variant has a stronger presence within biofilm cells than among planktonic cells (3). Our data are in agreement with this (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…S. mutans is organized on biofilms, where the cells are closely packed together and multiple species of microorganisms coexist. A previous study indicates that the S. mutans WIG Ϫ variant has a stronger presence within biofilm cells than among planktonic cells (3). Our data are in agreement with this (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown that recombination of gtfB and gtfC causes the formation of the WIG Ϫ strain and is RecA dependent (3). Previous studies with Streptococcus pneumoniae found the that recA gene was induced at competence (23,24), and competence-specific induction of recA was also demonstrated in Bacillus subtilis (22).…”
mentioning
confidence: 97%
“…23 Furthermore, S. mutans is able to demineralise hydroxyapatite, thus demonstrating its relevance in the development of caries. 1,8,24 This key role played by S. mutans in the formation of cariogenic biofilm is a hypothesis already accepted in dentistry, since it is the best explanation for caries aetiology. 25 Therefore, reducing the levels of this micro-organism in the oral cavity seems to be crucial for controlling caries in general.…”
Section: Discussionmentioning
confidence: 94%
“…It induces mineral loss due to its strong adhesion to the tooth surface and to the acid production resulting from fermentable carbohydrates, which keeps local pH low. 1 The biofilm produced by this pathogen accounts for S. mutans adhesion, and is therefore considered to be cariogenic as well. 2 Chlorhexidine (CHX) 3,4 and xylitol (XYL) 5 have been used as strategies to prevent and reduce carious lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive mutagenesis or natural selection of resistant cells may occur in bacterial biofilms and some evidence exists that these biofilms are responsible for the persistence of adapted strains in the industry or in human infections [47,48]. While the underlying mechanism of adaptation is not known exactly, biofilms are a source of natural diversity within bacterial populations [49].…”
Section: Sos Response and Biofilmsmentioning
confidence: 99%